5.6% lidocaine aerosol anesthesia for supragingival ultrasonic scaling in patients with chronic periodontitis or dental plaque-induced gingivitis - Xue Li; Qingxian Luan (Scientific Reports)
Abstract The aim of this study was to evaluate the efficacy and patient satisfaction of lidocaine aerosol for pain management during periodontal scaling and root planning in patients with chronic periodontitis or dental plaque-induced gingivitis. This study specifically concentrated on comparing the effectiveness of lidocaine aerosol as a topical anesthetic against a placebo, assessing its impact on pain perception during the procedure. Additionally, the relationship between periodontal treatment and the reduction of oxidative stress markers in these patients was assessed. Eighty-six patients with chronic periodontitis or dental plaque-induced gingivitis were included. Notably, 5.6% lidocaine and placebo aerosols were randomly applied to the labial (buccal) and lingual (palatal) sides, approximately 3 mm from the gingival surface, with three sprays on each side, prior to supragingival ultrasonic scaling in these patients. In this controlled, double-blind study, the effectiveness of a 5.6% lidocaine aerosol in reducing pain during supragingival ultrasonic scaling was evaluated. The study involved 50 patients who divided into two groups: one receiving the lidocaine aerosol and the other a placebo. Pain was assessed using the Visual Analog Scale (VAS) and the Numeric Rating Scale (NRS). The results revealed a statistically significant reduction in pain scores in the lidocaine group compared with the placebo group. Specifically, the mean VAS score in the lidocaine group was 2.1 ± 1.3, compared with 5.6 ± 1.7 in the placebo group (P < 0.01). Similarly, the NRS scores were significantly lower in the lidocaine group (2.3 ± 1.2) compared with the placebo group (5.9 ± 1.8, P < 0.01). No adverse reactions were found in none of the groups. 5.6% lidocaine aerosol holds promise as an effective anesthetic option for reducing pain during supragingival ultrasonic scaling procedures in patients with chronic periodontitis or dental plaque-induced gingivitis. Chinese Clinical Trial Registry (No. ChiCTR2000029831, date: 2020-02-15).